Determination of local fluid dynamic parameters in structured packings through X-ray tomography: Overcoming image resolution restrictions. (16th January 2021) - Bolenz, L.; Fischer, F.; Toye, D.; Kenig, E.Y.
Highlights: Tomographic measurements of liquid flow in structured packings for varying viscosities. A new method was proposed for an improved representation of liquid distribution. The film thickness strongly varies locally inside the packing. Wetting degree of structured packing was examined. Abstract: X-ray tomography is a powerful method for the noninvasive investigation of fluid dynamics in packed columns. However, for the quantitative determination of local fluid dynamic parameters, such as film thickness on packing sheets, the spatial resolution is often too low. In this work, tomographic measurements were carried out in a column of 100 mm diameter equipped with Mellapak 350.Y packings. Different working liquids with low surface tension and varying viscosity up to 50 mPa s were used. Methods for improving the representation of the dry structured packing sheets and the gas–liquid interface in the cross-sectional images are presented. They are applied to the tomographic images and allow overcoming image resolution restrictions, which results in accurate determination of film thickness and degree of wetting on the structured packing.